The August 2002 flood in Austria: sensitivity of precipitation forecast skill to areal and temporal averaging - Alexander Kann; Thomas Haiden (Meteorologische Zeitschrift, 2005)
The dependence of precipitation forecast skill on areal and temporal averaging during the August 2002 floods in Austria is investigated. Operational forecasts of the ALADIN limited area model are verified against precipitation analyses obtained from a combination of two different networks of surface stations: a hydrological network with good spatial coverage but limited temporal resolution (24 h), and a meteorological network with good temporal resolution (10 min) but limited spatial density. By applying averaging windows of varying size in space and time it is shown to what extent the forecast skill increases with decreasing forecast specificity. For the space and time scales studied an increase of the time window by a certain factor is found more efficient in reducing forecast error than an increase of area size by the same factor, reflecting well-known differences between the spatial and temporal autocorrelation of the precipitation process itself. Comparison with other moderate-to-heavy precipitation episodes of the period 1999–2002 shows close agreement, suggesting that the results are typical of such events in the region.